Akibat Hukum Mengenai Pencabutan Laporan Saat Pelaku Terbukti Bersalah Melakukan Tindak Pidana KDRT - Shirena Putri Brilianty; Abraham Ferry Rosando (Lembaga Pengembangan Kinerja Dosen, 2024)
According to the state, all constructs of crime, especially domestic crime, are included with human rights violations, crimes against human dignity and discriminatory practices. Domestic crime, usually abbreviated as domestic violence, is a phenomenon that often occurs in or around the family. The majority of domestic violence is experienced by women or children because there are many aspects of life that are less or even unfair to them, thus providing opportunities for crimes against them. Physical abuse or violence, exploitation, neglect, and sexual abuse by spouses, children, or household staff are just some of the many forms of domestic crimes that can occur. In real life, there are many documented and unusual instances of domestic abuse. The purpose of this research is to determine and assess the impact of withdrawing a domestic violence report on the legal standing of the perpetrator. To examine the ambiguous standards surrounding the revocation of domestic crime reports, this research was written using normative legal research techniques with a statutory approach. The research findings show that, in accordance with Article 44 of Law Number 23 Year 2004 on the Elimination of Domestic Violence, husbands who commit violence against their spouses can be subject to sanctions. Domestic crimes are included in the relative complaint offense but are only covered in Articles 51 and 52, which basically do not make it painful or difficult for someone to carry out daily activities or hold a job or other position. Shortly after the perpetrator was named as a suspect in this domestic violence case, the victim withdrew the domestic violence report. As a result, the revocation of this report has legal consequences with the issuance of a Letter of Termination of Investigation in accordance with Article 75 of the Criminal Code.